The Rebirth of Uzbekistan: Politics, Economy, and Society in the Post-Soviet Era by Resul Yalcin (UK: Ithaca Press, 2002. 349 pages.) (American Journal of Islam and Society, 2005)
It is very difficult to avoid the conclusion that instead of getting involvedin the broader democratization process, the new post-Soviet states ofCentral Asia have resisted such trends. At present, many of them, includingthe Republic of Uzbekistan, are considered the most authoritarian states inthe world. The Uzbek authorities’ savage and bloody suppression of a massivepeople’s protest on May 13, 2005, shocked the international community.After the Soviet Union’s disintegration, Uzbekistan became the onlyCentral Asian state with a prepared long-term strategy of economic reform.However, the overwhelming incompetence of the Uzbek leadership and theprevalent corruption among Uzbek officials caused the Uzbek model ofmarket economy, outlined by President Islam Karimov in the initial periodof reform, to fail.At first glance, it might seem rather ostentatious to claim that this bookis a first attempt to study systematically the political, economic, social, andcultural changes that have taken place in this country for the last decade.Indeed, since the Soviet Union’s collapse, hundreds of books and researcharticles on the current situation in the post-Soviet Muslim states have beenpublished. However, as Bogdan Szajkowski’s “Foreword” suggests, theauthor conducted his research with an acute and critical eye for facts anddetails (p. ix), which makes this book the first truly comprehensive study ofcontemporary Uzbekistan.The first chapter looks at Central Asia’s history, the period prior to itsannexation by the Russian Empire, and (very briefly) the decades of thelate-nineteenth and early-twentieth century prior to the Bolsheviks’takeover. The following chapters examine the main developments duringthe Soviet period and investigate the roots of Uzbekistan’s totalitarianregime. The author stresses that from the beginning, the Uzbek governmentignored the idea of a pluralist democracy. For example, the first manifestationsof an independent Uzbekistan, the student protests at the capital’suniversity in mid-January 1992 that, apparently, were triggered by the liberalizingspirit of the time and raised slogans of democratic political opposition,were brutally crushed.The Law on Political Parties, which came into force in December 1996,introduced a multi-party political system. At the same time, the Uzbek partysystem held the prospective parties in check. Yalcin writes that in the firststage of multi-partisanship (1991-93), Uzbekistan had three parties and onepolitical movement. By late 1993, two of them, the Erk Democratic Partyand the Birlik Movement, were banned and most of the opposition leaderswere exiled (pp. 54-56). Some prominent opposition figures were imprisonedand some simply disappeared from the political scene.At present, with the exception of the People’s Democratic Party ofUzbekistan (PDPU) that is the successor of the Communist Party of Soviet ...